Cultural Preservation Research: A Bibliometric Review - Loso Judijanto (West Science Interdisciplinary Studies, 2026)
Cultural preservation has become an increasingly important research area due to growing challenges associated with globalization, environmental change, technological transformation, and the degradation of cultural heritage assets. This study aims to examine the development, intellectual structure, and emerging research trends in cultural preservation through a bibliometric analysis approach. Data were collected from a scientific database and analyzed using bibliometric techniques, including performance analysis, keyword co-occurrence analysis, citation analysis, density visualization, and collaboration network analysis. The findings reveal that cultural preservation research has developed into an interdisciplinary field connecting heritage conservation, archaeology, architecture, tourism, sustainability, and digital technologies. The keyword analysis indicates that cultural heritage and historic preservation are the dominant themes, while emerging topics such as virtual reality, three-dimensional computer graphics, photogrammetry, sustainable development, and risk assessment reflect the increasing adoption of innovative preservation strategies. Citation analysis identifies influential studies focusing on digital documentation, heritage recording, climate change impacts, and immersive heritage experiences. Furthermore, collaboration analysis demonstrates the existence of international research networks, with countries such as the United States, Italy, Spain, France, and China playing important roles in advancing cultural preservation scholarship. This study contributes to a deeper understanding of the evolution of cultural preservation research and highlights future opportunities for integrating digital innovation, sustainability principles, and collaborative approaches to strengthen global heritage protection.